Análise da idade como fator de prognóstico de câncer de mama em estágios iniciais - Meller, Kelly Cristina (2012)
Breast cancer is the main cause of death from malignant neoplasia in women worldwide, with its incidence on constant growing. In most of developed countries its mortality is declining, but in Brazil, in spite of recent advances in the therapeutic arsenal for treatment of the disease, death follows in steadily increase. Breast cancer mostly affects women in their fourth decade of life with a peak incidence in the sixth decade, and, although it is less common before the age of 40, is still responsible for more than 30% of cancer cases in women with less than 40 years old. Several studies consider the disease that affect the younger patients has a poorer outcome with increased risk of death compared with women in older age. This study was designed in order to determine the incidence and prognosis of breast cancer in women under 40 years of age at diagnosis, and to compare the disease-free survival and overall survival in relation to patients over 40 years. To conduct the study were reviewed medical records of patients diagnosed with breast cancer of four tertiary institutions specialized in the treatment of cancer patients from different regions of Rio Grande do Sul, totaling 649 patients in between the years 1992 and 2011. The age ranged from 24 to 92 years, 87.82% being women over 40 years, and 12.17% being younger women. The results revealed a balance on the staging at the moment of diagnosis, however, on the group of younger patients there was a higher incidence of triple negative phenotype and lower incidence of hormone receptor positivity. In relation to the treatment received both groups were similar.The curves of disease-free survival and overall survival showed a clear tendency to an increased risk of relapse and death in patients under 40 years. The findings confirm the literature data that associate early age with a more aggressive disease, as the worst prognosis persists even after correction by staging and it seems not to change with more intensive treatments. These results lead us to believe that breast cancer is a heterogeneous disease that has different biological characteristics for the different age groups studied. Further studies are needed to better understand the disease in this age group, therefore allowing to modify the course of the pathology in these patients.